Assessing The Effectiveness Of Maritime Sustainability Initiatives: A Qualitative Study - Bambang Sumali; Tri Cahyadi; Andriyan Hendry Ole; Larsen Barasa; Erwin Ferry Manurung; Abdul Rachman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research examines the effectiveness of sustainability initiatives within the maritime sector, focusing on their environmental and economic impacts. Through qualitative analysis of perspectives from maritime professionals, educators, and graduates, the study identifies key successes and challenges in implementing sustainability programs. Larger maritime companies have shown significant progress in reducing greenhouse gas emissions and improving operational efficiency, while smaller enterprises face financial and logistical barriers to adopting green technologies. The study also highlights the gap between sustainability education and its practical application in the industry, calling for stronger collaboration between academic institutions and industry leaders. The findings underscore the need for continued innovation, policy support, and investment to ensure that sustainability initiatives contribute to both environmental preservation and long-term economic growth in the maritime sector.